Navigating The Publishing Landscape: Lived Experiences of Marketing Pro-fessionals in the Publishing Industry - Tojoy, Annabelle; Polinar, Mark Anthony N.; Delantar, Alexander Franco A. (Future Science / FSH-PH Publications, 2025)
The publishing industry is rapidly evolving, driven by digital advance-ments and shifting consumer demands. Marketing professionals are crucial in navigating these changes, employing innovative strategies to achieve the organization’s objectives. This phenomenology study ex-plores marketing professionals’ lived experiences and understanding of the meaning of their experiences in the publishing industry. Six (6) marketing professionals participated in the interview and were se-lected based on the set inclusions by the researchers. A structured in-terview guide was employed to unearth the participants' lived experi-ences and understand the essence of their responses, and Colaizzi’s method was used to generate the study’s themes. Subsequently, the study generated four key themes: (1) challenges encountered by a mar-keting professional, (2) marketing strategies utilized by a marketing pro-fessional, (3) motivational factors as fuel to a marketing professional, and (4) observed trends in the publishing industry. The overall results suggest that marketing professionals in the publishing sector are tasked with finding a balance between innovative creativity and adaptability to ongoing changes. They must adeptly leverage new trends and execute successful strategies while managing the challeng-es of a highly competitive and rapidly changing environment. To achieve success, these professionals should be resourceful and vision-ary, consistently enhancing their methods to address the needs of a dynamic market.